Beta2-adrenergic agonist use and the risk of multiple sclerosis: a total population-based case-control study. (October 2014) - Tsai, Ching-Piao; Lin, Feng-Cheng; Lee, Charles Tzu-Chi
Objective: The aim of this study was to investigate whether the use of fenoterol, a beta2-adrenergic agonist, was associated with multiple sclerosis (MS) risk by conducting a total population-based case-control study in Taiwan. Methods: A total of 578 patients with newly diagnosed MS who had a severely disabling disease (SDD) certificate between January 1, 2002 and December 1, 2008 comprised the case group. These cases were compared with 2890 gender-, age-, residence-, and insurance premium-matched controls. Fenoterol use was analyzed using a conditional logistic regression model that controlled for asthma, chronic obstructive pulmonary disease (COPD), salbutamol and steroid use. Results: Compared with the group of people who did not use fenoterol, the adjusted odds ratios were 0.67 (95% confidence interval (CI) = 0.48–0.93, p = 0.016) for the group prescribed fenoterol below 2.25 cumulative defined daily dose (cDDD) and 0.49 (95% CI = 0.33–0.71, p < 0.001) for the group with a cumulative fenoterol use of more than 2.25 cDDD. The dose-response relationship was similar within the non-asthma patients. The associations were similar between males and females, but differences between age groups were observed. Conclusions: The results of this study suggest that fenoterol use may reduce the risk of MS.